HUBUNGAN TINGKAT PENGETAHUAN IBU HAMIL TERHADAP PERILAKU PENCEGAHAN PENULARAN HIV/AIDS - Fifi Alviana; Romdiyah Romdiyah (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2020)
Purpose: To determine the relationship of the level of knowledge of the behavior of the prevention of maternal transmission of HIV / AIDS. Methods: The design of this study was non-experimental (observational) with a cross sectional design. The sampling technique used in this study is total sampling or sampling saturated with number 60 pregnant women. Data collection tool uses a questionnaire. Data analysis used univariate, biavariate and multivariate tests. Results: Respondents who have poor behavior in preventing transmission of HIV / AIDS among pregnant women is more prevalent among respondents who have a good knowledge 58.6% less than the respondents who have a good knowledge about the prevention of transmission of HIV / AIDS among pregnant women (29.0%) . Chi square test results obtained p = 0.021. Conclusion: There is a relationship between the level of knowledge of pregnant women with HIV / AIDS prevention behavior. Key word: HIV / AIDS, knowledge, pregnant women.